An oral hermeneutics within the lay preaching context of the Nkhoma Synod of the church of Central Africa Presbyterian (CCAP) : a critical evaluation - Chifungo, Davidson Kamayaya (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.